Electromyographic characteristics of muscles in children with malocclusion and disorders of the musculoskeletal system in the period of mixed bite - Smaglyuk, L.V.; Liakhovska , A.V. (Medicni Perspektivi, 2025)
The maxillofacial region, as a component of the stomatognathic system, is one of the links of a complex mechanism of postural control, and is closely related to other musculoskeletal and neural sensors, in particular the musculoskeletal system, under the control of the central nervous system. Electromyographic research is one of the leading diagnostic methods in dentistry, which allows to objectively assess muscle activity and, accordingly, the functional state of the maxillofacial region. The aim of the study was to determine the features of electromyographic activity of masticatory, mimic, sternocleidomastoid muscles in children with malocclusion and musculoskeletal disorders. The main group consisted of 26 children with malocclusion and musculoskeletal disorders. The average age was 9.5±1.8 years. There were 12 (46.2%) girls and 14 (53.8%) boys. The control group consisted of 20 children without malocclusion, musculoskeletal disorders and other somatic pathology, comparable in age and sex. The average age of the children was 9.2±1.6 years, there were 11 (55.0%) girls and 9 (45.5%) boys. All subjects of the main and control groups underwent surface electromyography of the temporal, masticatory, sternocleidomastoid, submental and orbicular muscle of mouth in the tests: maximum bilateral teeth clenching, swallowing, teeth clenching on the left side, teeth clenching on the right side. In children with malocclusion and musculoskeletal disorders, an imbalance of muscle work was established, both in tension tests (teeth clenching) and in swallowing functions. In the bilateral teeth clenching test, asymmetric, “cross” activity of the temporal, masticatory and sternocleidomastoid muscles on the left and right sides was diagnosed. In the test of the lateral teeth clenching in children of the main group, there was no significant difference between the electromyographic activity of the muscles of the working and balancing sides, which was observed in the control group and was accepted as physiologically normal activity in these tests. In the functional swallowing test of subjects of the main group, a significant increase in the electromyographic activity of the sternocleidomastoid, submental and orbicular muscle of the mouth was determined, which significantly exceeded the values of the control group (p>0.05). The electromyographic activity of the chewing muscles was low and asymmetric.